The Role of Antibodies Lipids in Antiphospholipid Abortion Occurred in Women with Toxoplasmosis in Kirkuk City - Bafreen Mohamad Raza (Journal of Global Pharma Technology, 2019)
In the study the level of antiphospholipin (APL) antibodies with T. gondii in 160 abortion women who clinically diagnosed with recurrent miscarriage their aged between 15– 45 years, attending to Kirkuk hospital and 20 pregnant women with good health had not been subjected to previous abortion were included as control in the study which extended from April 2017 to October 2017. Blood samples and the required information regarded with maternal age and number of previous miscarriage were collected from both patients and healthy. Shown from the results that 21 (13.13 %) cases of abortion women with previous miscarriage were positive in APL- IgG and 10 (6.25 %) cases of abortion women with recurrent previous miscarriage give for APL+ and T.gondii IgG +IgM, all test results give negative in healthy women. An obvious significant ant differences at probability level (P < 0.05) found when make comparison between (APL IgG, IgM) with T.gondii+ APL IgM, IgG in both patient and healthy. The highest percentage of abortions was in the age (15-25) group. The lowest number of abortions was within the age group (25-35) years. The overall rate was 31%. It was the proportion of antiphospholipin IgG+ 21% and%10 of (IgG+ IgM) for antiphospholipin with antibodies T.gondii. There was no case of acute infection IgM+ antibody.Keywords: Recurrent Abortion, Toxoplasma gondii, Antiphospholipid.